2016
DOI: 10.1093/bja/aew024
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine vs propofol-remifentanil conscious sedation for awake craniotomy: a prospective randomized controlled trial † †Euroanaesthesia Congress, May 31, 2015, Berlin, Germany, and Canadian Anesthesiologists’ Society Annual Meeting, June 20, 2015, Ottawa, Canada. ‡ ‡This Article is accompanied by Editorial Aew113.

Abstract: NCT01545297.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
61
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(66 citation statements)
references
References 63 publications
2
61
0
3
Order By: Relevance
“…Although opioids, anesthetics, and antihypertensive drugs are routinely used to maintain hemodynamic stability during the perioperative period, concerning adverse effects such as hypotension, bradycardia, nausea, vomiting, and respiratory depression as a result of overcompensation still arise. Several anesthetic techniques have been reported recently to solve this problem, however an ideal solution has not been reported so far (Osborn and Sebeo, 2010; Bekker et al, 2013; Akeju et al, 2014; Seemann et al, 2015; Goettel et al, 2016). Asleep-awake-asleep (AWA) is an available option for ASA I–II patients, in addition to general anesthesia (GA), commonly used in neurosurgery, which requires intraoperative monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Although opioids, anesthetics, and antihypertensive drugs are routinely used to maintain hemodynamic stability during the perioperative period, concerning adverse effects such as hypotension, bradycardia, nausea, vomiting, and respiratory depression as a result of overcompensation still arise. Several anesthetic techniques have been reported recently to solve this problem, however an ideal solution has not been reported so far (Osborn and Sebeo, 2010; Bekker et al, 2013; Akeju et al, 2014; Seemann et al, 2015; Goettel et al, 2016). Asleep-awake-asleep (AWA) is an available option for ASA I–II patients, in addition to general anesthesia (GA), commonly used in neurosurgery, which requires intraoperative monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…OFA with dexmedetomidine (Dex) significantly attenuated postoperative pain and reduced opioid requirements without causing respiratory depression in obese patients. 18 19 OFA was then proposed for awake neurosurgery 20 and various minor 21 or major surgeries. 22 Two meta-analyses have concluded that intraoperative Dex reduced postoperative pain and opioid consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Dexmedetomidine (Dex), a kind of α 2 adrenergic receptor agonist, was often used in craniotomy and associated with fewer respiratory adverse events in previous research [ 8 ]. Dex is considered to confer protective effects on ALI induced by intestinal ischemia reperfusion, sepsis, orthotopic autologous liver transplantation, or other diseases [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%